ARISTOTLE'S LOGIC AT THE UNIVERSITY OF BUFFALO'S DEPARTMENT OF PHILOSOPHY - John Corcoran (Ideas y Valores)
We begin with an introductory overview of contributions made by more than twenty scholars associated with the Philosophy Department at the University of Buffalo during the last half-century to our understanding and evaluation of Aristotle's logic. More well-known developments are merely mentioned in order to make room to focus on issues at the center of attention from the beginning: existential import and, more generally, the analysis of categorical propositions. I include a list of the UB scholars, a list of collaborators and supporters from fellowinstitutions, a bibliography of relevant publications by UB scholars, and a bibliography of important related works.